MADRASAH: LEARNING SOCIETY DAN CIVIL SOCIETY (Potret Madrasah Aliyah Negeri 3 Malang) - Basuki Basuki (Badan Litbang dan Diklat Kementerian Agama RI, 2008)
Pedagogic which we recognize in Indonesia these days is a real narrow, tight pedagogic and tends to see the education problem solely as a technical problem in class room. Though, the education essentially is processing of humanization of someone in family life, cyltured public now and future. Education can build a new democratic and having morale Indonesia public, as Indonesian public craving these days. This article with philosophic and historical approach will expose madrasah as education institute of Islam bearing from, by; and for public (communay based education) has potency in creating conducive climate for bearing the learning socieiy as foundation of civil society.